1997
DOI: 10.1093/ndt/12.3.514
|View full text |Cite
|
Sign up to set email alerts
|

High-dose alfacalcidol improves anaemia in patients on haemodialysis

Abstract: High-dose alfacalcidol is efficient in anaemic patients with moderate hyperparathyroidism on maintenance HD and has a direct effect on erythropoietic cells regardless of serum calcium and iPTH levels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
61
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(70 citation statements)
references
References 0 publications
2
61
2
Order By: Relevance
“…It has been previously shown that these can be ameliorated by a reduction in the frequency of bisphosphonate (alendronate) dosing. 25,26 An important adverse effect shown by previous studies to be associated with alfacalcidol is hypercalcaemia, 27,28 although this adverse effect was not seen in the present study. The percentage increases in serum 25-hydroxyvitamin D 3 levels in both study groups were very large in the present study, whereas the percentage changes in serum calcium concentrations were very small.…”
Section: Discussioncontrasting
confidence: 63%
“…It has been previously shown that these can be ameliorated by a reduction in the frequency of bisphosphonate (alendronate) dosing. 25,26 An important adverse effect shown by previous studies to be associated with alfacalcidol is hypercalcaemia, 27,28 although this adverse effect was not seen in the present study. The percentage increases in serum 25-hydroxyvitamin D 3 levels in both study groups were very large in the present study, whereas the percentage changes in serum calcium concentrations were very small.…”
Section: Discussioncontrasting
confidence: 63%
“…Infants' Hb level, serum Fe as well as 25(OH)D concentrations were increased after they were treated with intramuscular iron dextran (13) . Studies on patients with chronic kidney disease have also supported this association (14,15) .…”
mentioning
confidence: 85%
“…In many cases the correction of HPT in response to therapy avoids the need for parathyroidectomy and also improves the response to rHu-Epo in dialysis patients. This latter effect has been related to the control of HPT [4]. However, calcitriol (C) has been shown to improve anaemia without any correlation between parathyroid hormone levels and rHu-Epo requirement [5, 6].…”
Section: Introductionmentioning
confidence: 99%